Still available to subscribers! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
It is a daunting task to improve agricultural productivity with due consideration to environmental protection and traditional practices. Hugues Dupriez and Philippe De Leener made an outstanding contribution to this challenge through their five...